Development of leak-free phase change material aggregates - Drissi, Sarra; Ling, Tung Chai; Mo, Kim Hung (Elsevier, 2020)
This study aims to develop leak-free phase change material (PCM)-aggregates through a two-step pelletization process. Microencapsulated PCM (mPCM) was incorporated into the core of the aggregate during the granulation process and then coated with a PCM-free shell to overcome the PCM leakage. The thermal properties of pellets cured under CO2 and natural air, including their enthalpy and thermal conductivity as well as their thermal stability were measured and compared using differential scanning calorimeter, thermogravimetric analyses and transient plane source method. The effect of both mPCM content and CO2 curing on the strength of the aggregates was also analyzed. The results revealed that mPCM can be used to produce lightweight aggregates with a distinct core-shell structure having an oven-dry bulk density, water absorption and latent heat of about 788 kg/m3, 14% and 18 kJ/kg, respectively. In addition, the shell layer can effectively prevent the leakage of the PCM and can be further densified by CO2 curing. In addition, CO2 curing contributed to the improvement of the overall physical properties and early strength development of the aggregates. The developed leak-free PCM-aggregates would then allow adding PCM into the concrete mix as an inert material and hence suppress the degradation of mechanical strength and high-water demand caused by the direct use of mPCM in concrete. © 2019 Elsevier Ltd